A DC-DC Converter for Low Power Loads in Electric Vehicles - Farheen Mehnaz, Dr. Abdul Ahad Shaik , Vasu M (International Journal of Advanced Science and Technology, 2020)
Dual-voltage power system is required in electric vehicles to supply power to low power low voltage and high power and high voltage loads. Power to high power loads can be directly obtained from the battery bank where as a DC-DC converter is required to supply conventional low-power, low-voltage loads.  Several DC-DC converters such as isolated, non-isolated, half-bridge, full-bridge, and unidirectional and bidirectional topologies, for electric vehicles are available. The purpose of this paper to identify the best circuitry topology to design an advanced step-down DC/DC converters with the smallest mass, volume, highest efficiency and power.Keywords: DC-DC Converters, buck converter, Electric Vehicle